Association of Absolute Eosinophil Count and Post-Bronchodilator Reversibility in the Chronic Obstructive Pulmonary Disease Patients - Naveed, Muhammad; Azam Khan, Malik Nadeem; Shah, Syed Umer; Hussain, Altaf; Khan, Muhammad Shahid; Hussain, Muhammad Zahid (Pakistan Armed Forces Medical Journal, 2023)
Objective: To look for the relationship between absolute eosinophil count and post-bronchodilator reversibility in chronic obstructive pulmonary disease patients at Pak Emirates Military Hospital, Rawalpindi Pakistan. Study Design: Cross sectional study. Place and During of Study: Pulmonology Department, Pak Emirates Military Hospital Rawalpindi (PEMH) from Jul to Dec 2019. Methodology: The study was conducted on 150 patients suffering from chronic obstructive pulmonary disease admitted in the Medical Ward or reporting in the Outpatient Department. Lung function was assessed using spirometry pre- and postbronchodilation. The presence and severity of chronic obstructive pulmonary disease were assessed using modified Global Obstructive Lung Disease (GOLD) criteria. The presence of significant bronchodilator responsiveness was taken as ≥12% improvement in the forced expiratory volume (FEV) (1) or the forced vital capacity. Results: Of 150 patients in the final analysis, 95 (63.3%) were male, and 55(36.7%) were female. The mean duration of COPD in our target population was 9.13±1.23 years. 68 (45.3%) had >12% improvement after bronchodilator administration, while 82(54.7%) had <12% improvement. The absolute eosinophilic count was <2% in 49(32.7%), while it was raised in 101(67.3%) patients. Conclusion: Raised eosinophilic count emerged as a predictor of good response after administering bronchodilators among patients suffering from chronic obstructive airway disease. Screening patients for this simple blood component may predictresponse to the initial treatment and help in the tailoring of the treatment plan by the treating physician. Keywords: Chronic obstructive pulmonary disease, Eosinophils, Forced expiratory volume.